Improving the Business Environment in Latvia : The Impact of FIAS Assistance - Liepina, Sanda (World Bank, Washington, DC, 2017)
This paper tracks the process through which FIAS, the investment climate advisory service of the World Bank Group advised the government of Latvia from 1998 to 2004 on ways to improve the business environment, achieve higher rates of economic growth, and thereby alleviate poverty. This case study shows that it is reasonable to describe how assistance by FIAS led to an improved business environment. The role that FIAS advice played may be discerned at the level of benefits accruing to the target population (i.e., the amount of resources freed up by lower costs associated with administrative procedures). Whether these benefits accruing to the business community translated into higher rates of investment and productivity, and thus to higher economic growth and reduced poverty, is a function of the entire political, social, and economic structure in Latvia. It is evident that there are many links in the chain of causation, and that the direct attribution FIAS can claim diminishes at every step downstream from its activities. Credit for success must be shared with the Government of Latvia and its immediate stakeholders (i.e., the businesses and their associations), the European Union accession process, the input of many other complementary projects, market forces, and fortuitous timing.